Stopping the Bomb : The Sources and Effectiveness of US Nonproliferation Policy - Miller, Nicholas L., 1987- (Book collections on Project MUSE., 2018)
"Examines the history and effectiveness of US efforts to prevent the spread of nuclear weapons"--